The Effect of Supportive Leadership and Remote Working on Employee Productivity with Work-Life Balance as Intervening Variable - Dodik Jatmika; Muhammad Nurdin (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Flexible working practices and industrial digitalization are leading to trends in human resource management behaviors that have changed due to flexible work patterns, especially for digitalized organizations such as fintech companies. This is when organizations need to balance leadership and work-life in order to keep employees working. The purpose of this article is to study how supportive leadership and remote working affect employee productivity, including work and productivity, with work-life balance as the intervening variable. Quantitative analysis was conducted based on the Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) method. The participants of the study included 100 fintech firms’ employees who were recruited using a purposive sampling method. The findings reveal that supportive leadership and remote working are a potent and significant influence on individual workforce productivity. In addition, both variables are positively correlated with work-life balance, and work-life balance is known to positively influence employee productivity. In addition, work-life balance mediates the relationship between supportive leadership and remote working influence on employee productivity. This research suggests that productivity is a function of leadership support and work-life balance in flexible work systems, not just technical factors.